Genetic biomarkers identify a subgroup of high-risk patients within low-risk NPM1-mutated acute myeloid leukemia. Issue 5 (16th April 2021) - Carbonell, Diego; Suárez-González, Julia; Chicano, María; Andrés-Zayas, Cristina; Díez-Díez, Miriam; Rodríguez-Macías, Gabriela; Muñiz, Paula; Kwon, Mi; Anguita, Javier; Díez-Martín, José Luis; Buño, Ismael; Martínez-Laperche, Carolina
Abstract: Although acute myeloid leukemia (AML) with NPM1 mut /FLT3 -ITD neg is a low-risk entity, its relapse rate remains high. Out of 333 AML patients, 27 were NPM1 mut, and were analyzed in greater detail in order to find associations between clinical and molecular features and cumulative incidence of relapse. Next-generation sequencing (NGS) was performed on diagnosis and remission samples using two capture-based panels. The presence of the FLT3 D835 variant at diagnosis and a qPCR value of NPM1 mut ≥0.1% after induction chemotherapy were associated with an increased probability of relapse, especially if both conditions are present together. By contrast, patients in which the main clone found at diagnosis harbored NPM1 variant had a lower risk of relapse. Nineteen of the 85 variants found at diagnosis were detected by NGS in remission. AML Subgroup with NPM1 mut / FLT3 -ITD neg is a heterogeneous entity, which can be further risk-stratified based on molecular biomarkers.